2014
DOI: 10.1016/j.jcrs.2013.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tamsulosin on iris vasculature and morphology

Abstract: PURPOSE To determine whether preoperative iris vasculature and morphology are altered in patients who have taken tamsulosin (Flomax). SETTING Academic multispecialty practice. DESIGN Case series. METHODS Patients with current or past tamsulosin use and age- and sex-matched control patients were included. Anterior segment optical coherence tomography (AS-OCT) and iris fluorescein angiography were performed to measure iris vasculature and thickness before cataract surgery. Data collected at surgery include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Additionally, in vitro rabbit studies revealed that tamsulosin binds to melanin in the iris, causing atrophy of the dilator muscle, which could be a second mechanism leading to IFIS [18]. Alpha1A-ARs are also the most widespread adrenergic receptors in the arterioles of the iris, but a previous study using iris fluorescein angiography and anterior segment optical coherence tomography (AS-OCT) did not find evidence that tamsulosin use may lead to dysregulation of the iris vessels [19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in vitro rabbit studies revealed that tamsulosin binds to melanin in the iris, causing atrophy of the dilator muscle, which could be a second mechanism leading to IFIS [18]. Alpha1A-ARs are also the most widespread adrenergic receptors in the arterioles of the iris, but a previous study using iris fluorescein angiography and anterior segment optical coherence tomography (AS-OCT) did not find evidence that tamsulosin use may lead to dysregulation of the iris vessels [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although some other studies using AS-OCT describe changes in iris thickness associated with tamsulosin use in patients with glaucoma, 8 similar to Tufan et al, 15 they did not detect differences in iris thickness in their study. In contrast to the differences in pupil size seen by Tufan et al 15 on AS-OCT, Shtein et al 14 found that photopic pupil measurements on AS-OCT were not significantly different between patients who had taken tamsulosin and those who had not. Their clinical measurements of pharmacologically dilated pupil size before surgery found significantly smaller pupils in patients who had used tamsulosin than in control patients, in contrast to the findings in a study by Cooney et al 16 They believed that their study used stronger pharmacologic pupil dilators because patients were being prepared for surgery rather than being dilated in the clinic.…”
Section: Discussionmentioning
confidence: 83%
“…Shtein et al 14 used AS optical coherence tomography (AS-OCT) to assess iris morphology, including iris thickness and PD in patients using tamsulosin. Although some other studies using AS-OCT describe changes in iris thickness associated with tamsulosin use in patients with glaucoma, 8 similar to Tufan et al, 15 they did not detect differences in iris thickness in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis of Intraoperative Floppy Iris Syndrome (IFIS) seems to be related to progressive loss of iris muscle tone caused by atrophy of iris dilator muscle [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%